Инновационная литейная форма корпуса контейнера для транспортировки и хранения отработавшего ядерного топлива - Vasilyev A. S., Bogdanov D. M. (Scientific studies from theory to practice, 2017)
proposed innovative mold container body for transport and storage of spent nuclear fuel will reduce the probability of occurrence of casting defects and to provide better mechanical properties of the casting.
Keywords: отработавшее ядерное топливо; высокопрочный чугун; ductile iron; литейная форма; корпус контейнера; mold; container body; the spent nuclear fuel